The Shadow of Colonialism on Relations Between Immigrant Parents and Their Children’s Teachers - Ali, Mehrunnisa Ahmad (Alberta Journal of Educational Research, 2012)
Using a theoretical framework that integrates socio-cultural theory, postcolonial perspectives, and the ethic of care, we (a) characterize the relationship between immigrant parents and their children’s teachers, (b) offer reasons for the relationship, and (c) suggest some strategies for improving them. Several focus group discussions were held with both groups, in elementary as well as secondary schools. The analysis shows that immigrant parents and their children’s teachers view each other through lens shaped by their colonial legacies, and have different role and communicative expectations from each other based on prior assumptions and experiences. Both groups need to acknowledge and confront these differences, keeping in mind that mutually respectful relationships between them are crucial for children’s success in schools. Nous nous appuyons sur un cadre théorique qui intègre la théorie socioculturelle, des perspectives postcoloniales et l'éthique relative aux soins, nous (a) caractérisons le rapport entre les parents immigrants et les enseignants de leurs enfants, (b) offrons des raisons pour ce rapport et (c) proposons des stratégies pour les améliorer. Plusieurs discussions ont eu lieu avec les deux groupes, tant dans des écoles élémentaires que des écoles secondaires. L'analyse démontre que les parents immigrants et les enseignants de leurs enfants se perçoivent par le biais de leurs patrimoines coloniaux d'une part, et que leurs attentes relatives aux rôles et à la communication de part et d'autre sont différentes et reposent sur des hypothèses et expériences antérieures d'autre part. Compte tenu du rôle crucial des rapports mutuellement respectueux entre les parents et les enseignants dans la réussite des enfants à l'école, les deux groupes doivent reconnaitre ces différences et les affronter.